Role of CC Chemokines Subfamily in the Platinum Drugs Resistance Promotion in Cancer - Reyes, Maria E.; de La Fuente, Marjorie; Hermoso, Marcela; Ili, Carmen G.; Brebi, Priscilla (Frontiers in Immunology, 2020)
Cancer is a significant medical issue, being one of the main causes of mortality around the world. The therapies for this pathology depend on the stage in which the cancer is found, but it is usually diagnosed at an advanced stage in which the treatment is chemotherapy. Platinum drugs are among the most commonly used in therapy, unfortunately, one of the main obstacles to this treatment is the development of chemoresistance, which is the ability of cancer cells to evade the effects of drugs. Although some molecular mechanisms involved in resistance to platinum drugs are described, elucidation is still required of others. Secretion of inflammatory mediators such as cytokines and chemokines, by tumor microenvironment components or tumor cells, show direct influence on proliferation, metastasis and progression of cancer and are related to chemoresistance and poor prognosis. In this review, the general mechanisms associated with resistance to platinum drugs, inflammation on cancer development and chemoresistance in various types of cancer will be approached with special emphasis on the current history of CC chemokines subfamily-mediated chemoresistance.